Proposals for the use element of equipment military personnel in the conditions of radiation and chemical contamination - Gishkо H. B.; Tkachenkо М. D. (Honor and Law, 2019)
Proposals on the training of military personnel for action in the conditions of radiation and chemical contamination, as well as the effective use of the elements of their equipment, are provided. The proposals that may be reflected during the implementation of the Program for the creation of a complex of combat equipment of a serviceman of the Armed Forces of Ukraine are formed.